The personal files from public exams to become a headmaster of graded schools in 1932 as a source for history of education. A case study: the dossier of María Sánchez Arbós - Menguiano Rodríguez, Carlos (Historia y Memoria de la Educación, 2019)
The aim of this paper is to present and contextualize a new source that, until now, had remained ignored and in need of a systematic approach: the personal files from public exams for the post of headmaster of large graded schools in 1932. These were the only such exams convened during the Second Spanish Republic. The peculiar structure of the exams opens the path to a new methodological approach, consisting of treating each file as a life-archive practice in which every candidate selects, with considerable freedom, a series of fragments and documents with which they would construct and represent their professional identities, not only to the examining board but also to themselves. Lastly, this paper undertakes a case-study with the file of well-known teacher, María Sánchez Arbós. This case will allow us to gauge the methodological possibilities of our proposal for studying the construction and reconstruction of the professional identities of republican teachers by having the opportunity to compare the composition of her exam file elaborated in 1932 with another well-known source: her diary, which was published in the nineteen sixties.